215 First-in-man study evaluating the safety, tolerability, pharmacokinetics and concentrationQT analysis of the novel BTK inhibitor evobrutinib (M2951) in healthy volunteers. (April 2019) - Becker, Andreas D; Martin, Emily C; Ona, Victor; Mitchell, David Y; Patel, Anand C; Johne, Andreas
Abstract : Background: Brutons tyrosine kinase (BTK) regulates B-cell receptor signaling and is a rational target for B-cell driven pathologies, including SLE. Evobrutinib (M2951) is a highly specific, oral inhibitor of BTK that demonstrated efficacy in preclinical models of autoimmune disease. This first-in-man study investigated the safety, tolerability, and pharmacokinetics (PK) of evobrutinib in healthy volunteers and examined the relationship between evobrutinib exposure and changes in QT interval. Methods: This was a single-center, Phase I, double-blind, placebo-controlled trial. In Part 1, 48 healthy participants in six successive dose cohorts (25, 50, 100, 200, 350, 500 mg) were randomized (6:2) to a single oral dose of evobrutinib or placebo. In Part 2, 36 participants in three ascending dose cohorts (25, 75, 200 mg/day) were randomized (9:3) to evobrutinib or placebo once daily for 14 days. Safety and tolerability were assessed following single and multiple dosing, and PK parameters determined by non-compartmental methods. Change from baseline in QT interval was obtained from 12-lead electrocardiogram recordings and corrected for heart rate by Fridericias method (QTcF). Results: Treatment-emergent adverse events (TEAEs) with evobrutinib were mostly mild, occurring in 25% of participants after single dosing, and 48% after multiple dosing. The nature and incidence of TEAEs were similar among evobrutinib and placebo groups, with no apparent dose relationship regarding the frequency or type of TEAEs. Evobrutinib showed rapid absorption (tmax ~0.5 hour), short half-life (~2 hour), and dose-proportional PK following single and multiple dosing, with no accumulation or time dependency on repeat dosing. ConcentrationQTcF analyses revealed no significant exposureeffect relationship. Based on a linear mixed-effects model for change from baseline in QTcF (QTcF), the slope of the relationship between mean placebo-adjusted QTcF (QTcF) and concentration was negative and close to zero (0.00027 ms/ng/mL; p=0.86; figure 1 ). The predicted QTcF effect at geometric mean Cmax for the highest dose (1512 ng/mL) was 1.16 ms, with an upper limit of 3.26 ms for the 90% two-sided bootstrapped confidence interval, which is well below the 10 ms threshold of regulatory concern (ICH-E14 guidance). Conclusions: Evobrutinib was well-tolerated in healthy volunteers, with predictable PK and no prolongation of QT interval (QTcF). Evobrutinib is undergoing clinical investigation in SLE and other autoimmune diseases. Funding Source(s): Merck KGaA, Darmstadt, Germany